Pengaruh ESG risk rating score, ukuran perusahaan, leverage, dan likuiditas terhadap kinerja keuangan perusahaan - Amelia Oktrivina; Sri Ambarwati; Elly Rosdiana (LPMP Imperium, 2024)
This study addresses the issue of sustainability, which has increasingly become a central focus for companies in their operational activities. One form of accountability for implementing sustainability is the disclosure of Environmental, Social, and Governance (ESG) values in sustainability reports. The ESG risk rating score serves as an indicator to evaluate how effectively a company manages risks across these three aspects. This research aims to examine the influence of ESG risk rating, company size, leverage, and liquidity on the financial performance of firms listed in the ESG Leaders Index from 2020 to 2023. The data was obtained from the Indonesia Stock Exchange using a purposive sampling technique, resulting in 60 observations from 15 companies over four years. The analysis method employed is multiple linear regression. The findings indicate that the ESG risk rating score and company size significantly negatively impact financial performance. In contrast, leverage and liquidity demonstrate a significant favorable influence on the economic performance of the companies. Public interest statements This study provides a foundational reference for future research and aids practitioners in understanding critical factors influencing financial performance. It enhances financial decision-making by offering insights that contribute to academic literature and practical applications within finance. This research ultimately supports organizations in improving their sustainability practices and economic outcomes.